Born early or too late ? : James Sheridan knowles and the Nineteenth century literary marketplace - Ramadan, Susanne; Shraah, Mahmoud (اتحاد الجامعات العربية - الجمعية العلمية لكليات الآداب, 2010)
تتناول هذه الدراسة الكاتب المسرحي جيمس شريدن نولز (1784-1862)، الذي ذاع صيته بين ادباء عصره فى بريطانيا خلال القرن التاسع عشر. وقد اعتقد ان نولز قد توقف عن الإنتاج الدرامي في سنوات حياته الاخيرة، بسبب انتقاله للكنيسة المعمدانية التي ترفض الفن والأدب كلياً. \ وجاءت هذه الدراسة، لتبين الأسباب الحقيقية التي كانت وراء تخلي نولز عن كتابة المسرح، وتتمثل بأربعة اسباب رئيسة؛ منها المراقبة الحكومية وقانون الترخيص الدرامي الصارم. وفندت الدراسة الاعتقاد السائد الذي كان يؤكد على أن إيمانه الجديد كان وراء تخليه عن المسرح. The following study presents the Victorian playwright and actor James Sheridan Knowles (1784 - 1862), who was one of the most well-known dramatists of the nineteenth century. Late in his lifetime, Knowles converted to the Baptist faith and gave up his career as playwright and actor. Sources on Knowles and his age have to this point maintained that Knowles became an ordained Baptist minister and abandoned the stage entirely because of his change of faith. This research will prove otherwise. It will expose the actual factors that drove Knowles to give up playwriting and it will refute previous assumptions about Knowles's desertion of the stage during the last years of his life. \ James Sheridan Knowles, the famous nineteenth century playwright, had long been neglected by scholars. Only less than a handful of scholarly studies on Knowles are available and all have maintained that Knowles abandoned the stage in favor of the pulpit due to his conversion to the Baptist faith in 1845. His son, Richard B. Knowles published a biography on his father, The Life of James Sheridan Knowles, in 1872 he asserts that his father retired from the stage because of his new faith. Leslie H. Meeks's specialized study on Knowles reaffirms Richard B. Knowles's claim that Sheridan Knowles gave up his literary career in favor of his new faith. Dictionaries, Encyclopedias, and resources on Victorian theatre all confirm this assumption(1). This study will shed new light on Knowles's late career change delving into the actual motives behind the playwright's decision to retire from the stage during the last seventeen years of his life.
Keywords: الأدب الإنجليزي -- الأدباء الإنجليز -- النقد الأدبي -- تولز ، جيمس شريدان